Picosecond Dynamics of CN - -Ligated Ferric Cytochrome c after Photoexcitation Using Time-resolved Vibrational Spectroscopy - Kim, Joo-Young; Park, Jae-Heung; Chowdhury, Salina A.; Lim, Man-Ho (Bulletin of the Korean Chemical Society, 2010)
The dynamics of the CN‒-ligated ferric cytochrome c (CytcCN) in D2O at 283 K following Q-band photoexcitation at 575 nm was observed using femtosecond time-resolved vibrational spectroscopy. The equilibrium vibrational spectrum of the CN stretching mode of CytcCN shows two overlapping bands: one main band (82%) at 2122 cm‒1 with 23 cm‒1 full width at half maximum (fwhm) and the other band (18%) at 2116 cm‒1 with 7 cm‒1 fwhm. The timeresolved spectra show bleaching of the CN fundamental mode of CytcCN and two bsorption features at lower energies.The bleach signal and both absorption features are all formed within the time resolution of the experiment (< 200 fs) and decay with a life time of 1.9 ps. One transient absorption feature, appearing immediately red to the bleach signal, results from the thermal excitation of low-frequency modes of the heme that anharmonically couple to the CN fundamental mode, thereby shifting the CN mode to lower energies. The shift of the CN mode decays with a lifetime of 2 ps, equivalent to the time scale for vibrational cooling of the low-frequency heme modes. The other transient absorption feature, which is 3.3 times weaker than the bleach signal and shifted 27 cm‒1 toward lower energies, is attributed to the CN mode in an electronically excited state where the CN bond is weakened with a lowered extinction coefficient. These observations suggest that photoexcited CytcCN mainly undergoes ultrafast radiationless relaxation, causing photo-deligation of CN‒ from CytcCN highly inefficient. As also observed in CN‒-ligated myoglobin, inefficient ligand photodissociation might be a general property of CN‒-ligated ferric hemes. KCI Citation Count: 8